Finite element analysis of plate placement in canine elbow arthrodesis: comparison of caudal, medial, and lateral applications - Shin, Junggyu; Ko, Jongchan; Heo, Suyoung (Frontiers in Veterinary Science, 2026)
IntroductionCanine elbow arthrodesis is a salvage procedure that reduces pain while preserving minimal limb function. Historically, plates have been applied to the caudal aspect, but recent techniques have introduced plate application to the lateral and medial aspects. However, biomechanical rigidity comparisons between these methods have not yet been conducted. Elbow arthrodesis involves difficulty in plate contouring. In this study, a custom plate model was designed, and 10 models were classified on the basis of plate position, plate length, and the presence of additional fixation to the radius. Finite element analysis was used to compare the rigidity of each model.Materials and methodsA custom plate model was designed, and 10 finite element models were created based on CT data of a canine elbow. Models were categorized by plate position (caudal, medial, lateral), plate length (short vs. long), and the presence of additional radius fixation. An axial force of 150 N was applied to simulate loading, and peak von Mises stress and strain in the plate and bones (humerus, radius, ulna) were measured and compared across models.ResultsMedial plate application demonstrated the highest rigidity in the plate, followed by lateral and then caudal application. In bone evaluation, the humerus and ulna showed greater rigidity with medial application. Rigidity of both plate and bone models increased with longer plate length and with additional fixation to the radius. For the radius, lateral fixation provided the greatest rigidity among groups with radius fixation.DiscussionFinite element analysis suggests that medial plate application provides superior biomechanical rigidity in canine elbow arthrodesis. Furthermore, utilizing a longer plate and incorporating additional fixation to the radius can enhance the overall biomechanical rigidity of the construct.